ON THE ISSUE OF IMPROVING TEMPORARY PROSTHETICS IN PATIENTS USING DENTAL IMPLANTS - Akhmedova A.A.; Safarov M.T.; Matmuradov M.K. (Scholar Express Journals, 2025)
The development of dental implantation has led to the need for improvement of temporary prosthetics, providing not only protection of the implant but also optimal conditions for its adaptation. Modern methods of producing temporary structures minimize the risks of inflammatory processes, improve aesthetic characteristics, and increase the level of comfort for the patient.
Keywords: prosthetics; implants; dentistry